Vibration Transmission across Seismically Damaged Beam-to-Column Junctions of Reinforced Concrete Using Statistical Energy Analysis - Marios Filippoupolitis; Carl Hopkins (Vibration, 2023)
To detect human survivors trapped in buildings after earthquakes by using structure-borne sound it is necessary to have knowledge of vibration transmission in collapsed and fragmented reinforced-concrete buildings. In this paper, statistical energy analysis (SEA) is considered for modelling vibration transmission in seismically damaged, reinforced concrete, beam-to-column junctions where the connection between the beam and the column is made only via the steel reinforcement. An ensemble of 30 randomly damaged beam-to-column junctions was generated using a Monte Carlo simulation with FEM. Experimental SEA (ESEA) is then considered with two or three subsystems to determine the coupling loss factors (CLFs) between the beam and the column with either bending modes or the combination of all mode types. It is shown that bending modes dominate the dynamic response and that the uncertainty of predicting the CLFs using FEM with ESEA is sufficiently low that it should be feasible to estimate the coupling even when the exact angle between the beam and the column is unknown. In addition, the use of two rather than three subsystems for the junction significantly decreases the number of negative coupling loss factors with ESEA. An initial analysis of the results in this paper was presented at the 50th International Congress and Exposition on Noise Control Engineering.